Influência do tempo de condicionamento e viscosidade do ácido metafosfórico 40% nas propriedades adesivas da interface radicular - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
In-vitro evaluation the influence of the different conditioner times (7 and 15 seconds) of 40% meta-phosphoric acid (MPA) and 37% ortho-phosphoric acid (OPA) in different viscosities (gel and liquid) on the adhesive properties of the root interface. Seventy-two roots of human premolars were endodontically prepared and randomly assigned into the 8 experimental conditions (n = 9) according to the combination of the variables: Acid [37% ortho-phosphoric acid (OPA) and 40 meta-phosphoric acid (MPA)]; acid viscosity [(gel (G) and liquid (L)]; and application times (7 and 15 s). The adhesive system Ambar Universal was applied and the fiber post were cemented with dual cement Allcem Core. After cementation, the teeth were cross-sectioned into slices and subjected to the pushout bond strength test (BS) (n = 6) at a speed (0.5 mm/min). For the nanoleakage (NL) evaluation, slices was randomly selected from each group and were immersed in silver nitrate solution for analysis by Scanning Electron Microscopy (SEM). For morphological analysis of the root surface, the teeth that were not cemented (n = 8) were randomly allocated according to each experimental condition and analyzed by SEM after acid etching. Data from BS and NL were submitted to ANOVA 3 factors and Tukey's test (􀀁 = 0.05). MPA showed similar values of BS to OPA, regardless of the application time and viscosity used (p < 0.001). The increase of application time resulted in a statistically higher BS values (p < 0.001). OPA increased the values of NL when compared with MPA (p < 0.001). When the viscosity was compared, regardless of the acid used, the liquid acid promoted a significant increase in the silver nitrate. (p < 0.05). The increase of the time of application of the OPA resulted in a significant increase of NL (p < 0.01). The use of 40% MPA promoted a similar BS, regardless of the viscosity and application time with lower NL than the 37% OPA.
Influence of the conditioner time and viscosity of 40% metaphosphoric acid on the adhesive properties of the root interface
Keywords: Ácido metafosfórico; Ácido ortofosfórico; Resistência de união; Nanoinfiltração; Condicionamento dentinário; Ortho-phosporic acid; Meta-phosphoric acid; Tensile bond strength; Nanoleakage; Dentin etching; CNPQ::CIENCIAS DA SAUDE::ODONTOLOGIA